“Who Cancelled Lee Highway?”: Expressions of White Racial Frames and Counterframes on Nextdoor - Maskell, Shayna (Journal of Ethnic and Cultural Studies, 2024)
In July of 2021, the Arlington County Board, just outside of Washington, DC, voted to change a major thoroughfare – previously known as Lee Highway – to Langston Boulevard. Despite this well-publicized and openly debated name change, the sight of the new road caused an uproar on the neighborhood social media site, Nextdoor. While social media sites have been central to the mobilization efforts of racial justice activists, these same sites are also often fundamental to a growing and more visible community of white supremacists. This study focuses on the ways in which geographic proximity, through the social media site Nextdoor, constructs community-based expressions of racial justice and whiteness. Using the 151 posts and responses that were published on Nextdoor the day after the street name change in a neighborhood in Arlington, VA, this study analyses how a primarily white, upper-class neighborhood publicly communicates its understanding of race and racial justice. This study was grounded in Feagin’s (2020) concept of the white racial frame, an overarching white worldview dominant in the Global North that embraces a broad and persisting set of racial stereotypes and ideologies. Findings suggest community members engaged in equal numbers in white racial frames and counterframes. Within the white racial frames, community members used whiteness as virtuousness and non-whiteness as unvirtuous, while counter-frames primarily relied on unveiling the white racial frames used. These findings indicate the ways in which social media as a form of communication works to reinforce existing spatial hierarchies while also reimagining community participation.